Management Optimization for Strengthening Catur Kintamani Tourism Village - Ni Made WAHYUNI; I Wayan Wesna ASTARA; Kadek Goldina Puteri DEWI (Indonesia Strategic Sustainability, 2023)
Catur Kintamani Village has been designated as a tourist village based on Bangli Regent Regulation Number 4 of 2018. Tourism trips with beautiful rural nature are the turning point for developing rural tourism. The situation analysis found that the tourism village faced the challenge of low local and domestic tourist visits, economic opportunities. Low intention to visit is influenced by management practices. Research has found that visits increase profits(Abbasi-Moud, Vahdat-Nejad, & Sadri, 2021). On the other hand, intense business competition, societal behavior and lifestyles put pressure on organizations to introduce alternative management to provide intentions to visit. The purpose of this community service is to strengthen the tourist village as an economic institution. The selected partner is a tourism awareness group (Pokdarwis). Through a series of participatory training methods attended by 5 participants, partners' knowledge and skills in the field of tourist destination management increased. The results of management optimization education and training show an increase in competence in marketing, human resource management, operations and financial management. PKM activity increases knowledge insight, changes in behavior of marketers, manages resources (natural and human) and finances. In the future, similar activities are needed with a focus on marketing management to sustainable tourism.